Discrete-time adaptive fuzzy speed regulation control for induction motors with input saturation via command filtering. Issue 12 (August 2019) - Wang, Mengmeng; Yu, Jinpeng; Ma, Yumei; Yu, Haisheng; Lin, Chong
Abstract: A discrete-time adaptive fuzzy control method is introduced to achieve the speed regulation for induction motors (IMs) with input saturation via command filtering in this paper. First, the continuous model of IMs drive system is transformed into discrete-time form by using Euler formula. Then, the fuzzy logic systems are used to approximate the unknown nonlinear functions in the discrete-time drive system. In addition, the command filtering control method is introduced to overcome the "explosion of complexity" problem in the design process of traditional backstepping method. It is verified that all the closed-loop signals are bounded and the outputs can track the given reference signals well. Finally, simulation results illustrate the validity of the discrete-time control method.